Differences between FIN 48 and IFRIC 23 A Critical Analysis - Seibert, Carolin (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Gabler, 2022)
Uncertainties about the tax treatment of business transactions in the tax return or tax balance sheet can cause significant accounting challenges for current and deferred taxes in the financial statements. Whereas the accounting treatment of tax risks or tax audit risks has been regulated under US GAAP since 2006, a corresponding IFRS regulation was only published in 2017 and is effective from the 2019 fiscal year. The author takes this as an opportunity to analyze and critically assess the differences between the US GAAP accounting regulation "FIN 48 - Accounting for Uncertainty in Income Taxes" and the IFRS accounting regulation "IFRIC 23 - Uncertainty over Income Tax Treatments". Building on the insights from her analysis, the author also examines the problem areas arising from IFRIC 23 from the perspective of the German tax authorities, German business practice and German advisory practice. About the author Carolin Seibert graduated with a Master of Science in Business Administration from the University of Münster, Germany. Currently, she works as a tax assistant and is pursuing her PhD at the Institute of Corporate Taxation and Accounting at the University of Trier, Germany. Her work and research focus on international tax law.
Introduction -- Conceptual Basis for Accounting for Uncertain Tax Positions -- Critical Analysis of the Conceptual Differences between FIN 48 and IFRIC 23 -- Critical Analysis of the Practical Application of IFRIC 23 -- Conclusion.
Keywords: Auditing; Auditing